DAKWAH COMMUNICATION STRATEGY TO VISUALLY IMPAIRED DISABILITIES: Case Study at the Qur'an Museum and Disability Qur'an Study Center (PSQD) Jember - Mohammad Rifky Reza Salim (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
In a broader sense, da'wah calls upon us to convey messages to humanity, including individuals with visual impairments. The da'wah messages are diverse, encompassing both Divine words (the Qur'an) and the sayings of the Prophet (al-Hadith). However, in the current context, da'wah to visually impaired individuals, especially in learning the Braille Qur'an, has received limited attention. Effective communication strategies are essential to enhance da'wah's efforts for this community of visually impaired individuals. The research adopts a qualitative descriptive approach, as it aims to provide an in-depth understanding of communication strategies in da'wah and their role in improving the Braille Qur'an reading abilities of visually impaired individuals, with a case study of the Quran Museum and the Da'wah Center for Disability Quran Studies (PSQD) in Jember.